A Comprehensive Review on Cascaded H-bridge Inverter-Based Large-Scale Grid-Connected Photovoltaic. Issue 5 (3rd September 2017) - Ray, Soumyadeep; Gupta, Nitin; Gupta, Ram Avtar
ABSTRACT: Large-scale grid-connected photovoltaic (PV) systems are facing issues like increment of efficiency, minimization of cost, and robustness of the total system. PV strings should operate at maximum power point in all weather conditions to make an efficient system. Inverter is one of the main components along with PV string in grid-connected PV system. Two-level inverters are normally used for practical implementation; however, multilevel inverters, especially cascaded H-bridge (CHB) inverter is one of the best alternative solutions available for large-scale PV plants keeping cost and efficiency in mind. CHB inverters generate a higher voltage output based on series connection of lower voltage H-bridge cells and also having features like higher modularity in structure. High-quality input current and output voltage can be obtained with lower rating devices in CHB-based system. CHB inverters are successfully used in high-power medium voltage drives, STATCOM, and active filter, but CHB-based PV system is facing great challenges in DC voltage balancing, active and reactive power control. This paper presents a comprehensive review on CHB-based large-scale grid-connected PV system. Different topologies and control techniques are reviewed thoroughly to justify potential of CHB-based PV inverters to replace conventional two-level grid-tied large-scale PV inverter. A list of 88 research papers is appended based on advancement, various topologies, and control technique on this area and classified for reference.